Новые виды гименолепидид (Cestoda, Hymenolepididae) от пегого путорака - Великанов, В.П.; Ткач, В.В. (Вестник зоологии, 1993)
Staphylocystis putoraki sp. n. and S. diplomesodoni sp. n. are described from Turkestan desert shrew (Diplomesodon pulchellum) from Turkmenistan and Kazakhstan. Some questions of Hymenolepidid systematics and hostal specificity are discussed.